2019
DOI: 10.1002/ecs2.2737
|View full text |Cite
|
Sign up to set email alerts
|

Water clarity and temperature effects on walleye safe harvest: an empirical test of the safe operating space concept

Abstract: Successful management of natural resources requires local action that adapts to larger‐scale environmental changes in order to maintain populations within the safe operating space (SOS) of acceptable conditions. Here, we identify the boundaries of the SOS for a managed freshwater fishery in the first empirical test of the SOS concept applied to management of harvested resources. Walleye (Sander vitreus) are popular sport fish with declining populations in many North American lakes, and understanding the causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 36 publications
(92 reference statements)
0
45
0
Order By: Relevance
“…This result is not surprising because walleye have evolved subretinal tapetum lucidum that allow them to feed, grow, and reproduce at low light levels (Ryder 1977;Lester et al 2004). Other studies have found that walleye population biomass is greater in dark lakes (Lester et al 2004;Hansen et al 2019).…”
Section: Walleye Productionmentioning
confidence: 89%
“…This result is not surprising because walleye have evolved subretinal tapetum lucidum that allow them to feed, grow, and reproduce at low light levels (Ryder 1977;Lester et al 2004). Other studies have found that walleye population biomass is greater in dark lakes (Lester et al 2004;Hansen et al 2019).…”
Section: Walleye Productionmentioning
confidence: 89%
“…), and habitat loss (Hansen et al. ). Regardless of the mechanism, the lack of Walleye recruitment is concerning, as it creates problems for sustainable Walleye fisheries.…”
mentioning
confidence: 99%
“…Fish populations are largely regulated through recruitment patterns (Ricker 1975); however, Walleye recruitment is declining in some locations (Hansen et al 2017;Rypel et al 2018), whereas Walleye cannot naturally reproduce or their recruitment is limited in other locations (Mitzner 2002;Reed and Staples 2017;Koch et al 2018). Although the reasons for poor recruitment are not clear, potential mechanisms that have been hypothesized include competition or predation (Fayram et al 2005;Fielder et al 2007), climate variability (Beard et al 2003;Hansen et al 2017), and habitat loss (Hansen et al 2019). Regardless of the mechanism, the lack of Walleye recruitment is concerning, as it creates problems for sustainable Walleye fisheries.…”
mentioning
confidence: 99%
“…A. Hansen et al, 2019). Yet these sorts of dynamics received very little attention in the studies that we reviewed.…”
Section: Frontier 3: Resilience Thinkingmentioning
confidence: 94%